Is What’s “Trending” What’s Worth Purchasing?: Insights From a National Study of Collection Development Librarians - Sutton, Sarah W.; Miles, Rachel A.; Konkiel, Stacy (My University, 2017)
New forms of data like altmetrics are helping librarians to make smarter decisions about their collections. A recent nationwide study administered to librarians at R1 universities shines light on exactly how these metrics are being applied in academia. This article is based on a presentation from the NASIG 31st Annual Conference. It includes survey results addressing previously unknown rates of technology and metrics uptake among collection development librarians, the most popular citation databases and altmetrics services being used to make decisions, and surprising factors that affect attitudes toward the use of metrics.
Citation: Sutton, S., Miles, R., & Konkiel, S. (2017). Is What’s “Trending” What’s Worth Purchasing?: Insights From a National study of Collection Development Librarians. The Serials Librarian, 72, (1-2). http://dx.doi.org/10.1080/0361526X.2017.1297593
Keywords: altmetrics; bibliometrics; collection development; selection criteria; survey research; academic libraries